Ovarian ROS-dependent IgG accumulation precedes lipofuscin deposition and follicular decline: comparative insights from the bitch and mouse models of ovarian aging - Montenegro, Luís; Rigos, Natália; Brandão, Catarina; Pinto, Anabela; Borges, Inês; Cardoso, Luís; Carvalho, Hugo; Almeida, Henrique; Martins-Bessa, Ana; Silva, Elisabete (Frontiers in Aging, 2025)
IntroductionIn the ovaries, inflammation, oxidative stress, fibrosis and a unique population of multinucleated giant cells have been linked to aging. However, the role of IgG deposition is unknown. Using the dog to study aging is relevant as bitches experience age-related fertility loss and share similar environmental conditions with humans. Therefore, the bitch was used to study reproductive aging. The present work hypothesized that the deposition of multinucleated giant cells and the accumulation of IgGs in the ovary contribute to aging. The objectives were to identify these markers in the ovaries of bitches and correlate them with aging, and to assess whether antioxidants could modulate age-dependent IgG accumulation.MethodsOvaries from bitches (from 6 months to 13 years, divided into three groups: <2 years, 2–6 years, and >6 years) and from mice [aged 8–12 weeks–young and 38–42 weeks–reproductively aged (vehicle or apocynin treated)] were employed. Hematoxylin and eosin staining was used to evaluate the ovarian follicle reserve pool. Sudan Black B (SBB) staining identified and characterized the accumulation of lipofuscin, a marker present in ovarian multinucleated giant cells. Immunohistochemistry was employed to determine IgG deposition and western blotting for its quantification. The Kruskal-Wallis and Mann-Whitney-U tests were used for multiple comparisons. The Spearman correlation coefficient measured correlations between the studied variables.ResultsIn the bitch, reproductive aging associates with a decrease in follicle pool, an increase in multinucleated giant cells, and an increase in IgG accumulation. Ovarian deposition of lipofuscin was significantly higher in bitches over 2 years of age, whereas IgG deposition was only significant in the >6 years group. Unlike SBB staining, which was absent in the <2 years group, IgG accumulation was already detected in younger animals. In the mice, ovarian IgG staining was increased in reproductively aged animals, but not in reproductively aged animals treated with apocynin.ConclusionThis study indicates that IgG deposition is an early event that precedes and possibly triggers the recruitment of macrophages. These findings provide new insights into mechanisms of ovarian aging and the use of antioxidants as a strategy to mitigate it.